Modelling electro-osmosis–surcharge preloading combined consolidation of unsaturated soils. (October 2019) - Zhou, Yadong; Deng, An; Fu, Jiyu
Abstract: Electro-osmosis often dewaters soils into unsaturated conditions. The unsaturated conditions invalidate electro-osmosis models that are developed by assuming presence of full saturation throughout. The unsaturated condition causes non-negligible influences on soil geomechanical properties and its consolidation behaviour, and should be accounted for. This study presents a numerical model, UEC2, of simulating electro-osmosis–surcharge preloading combined consolidation considering varied degree of saturation of soil. Model UEC2 is able to capture nonlinear changes of soil properties, time-dependent loading and instantaneous pore air compression. This model was validated against laboratory test results, and was applied to varied test examples in order to assess evolvement of unsaturated conditions and its effect on consolidation.